Longitudinal Follow-Up With Radiologic Screening for Recurrence and Secondary Hiatal Hernia in Neonates With Open Repair of Congenital Diaphragmatic Hernia—A Large Prospective, Observational Cohort Study at One Referral Center - Zahn, Katrin B.; Schaible, Thomas; Rafat, Neysan; Weis, Meike; Weiss, Christel; Wessel, Lucas (Frontiers in Pediatrics, 2021)
After neonatal repair of congenital diaphragmatic hernia (CDH) recurrence is the most severe surgical complication and reported in up to 50% after patch implantation. Previous studies are difficult to compare due to differences in surgical techniques, retrospective study design, lack of standardized follow-up or radiologic imaging. The aim was to reliably detect complication rate by radiologic screening during longitudinal follow-up after neonatal open repair of CDH and to determine possible risk factors. At our referral center with standardized treatment algorithm and follow-up program consecutive neonates were screened for recurrence by radiologic imaging at defined intervals during a 12-year period. 326 neonates with open CDH-repair completed follow-up of a minimum of two years. 68 patients (21%) received a primary repair, 251 (77%) a broad cone-shaped patch and seven a flat patch (2%). Recurrence occurred in three patients (0.7%) until discharge and diaphragmatic complications in 28 (8.6%) thereafter. Overall 38 recurrences and/or secondary hiatal hernias were diagnosed (9% after primary repair, 12.7% after cone-shaped patch; p=0.53). Diaphragmatic complications were significantly associated with initial defect size (r=0.26). In multivariate analysis left-sided CDH, an abdominal wall patch and age below four years were identified as independent risk factors. Accordingly, relative risks were significantly increased (left-sided CDH: 8.5 (p=0.03); abdominal wall patch: 3.2 (p<0.001); age ≤4 years: 6.5 (p<0.002)). 97% of patients with diaphragmatic complications showed no or nonspecific symptoms and 45% occurred beyond one year of age. Long-term complication rate after CDH-repair highly depends on surgical technique: a comparatively low recurrence rate seems to be achievable in large defects by implantation of a broad cone-shaped, non-absorbable patch. Longitudinal follow-up with regular radiologic imaging until adolescence is essential to reliably detect recurrence to prevent acute incarceration and chronic gastrointestinal morbidity with their impact on prognosis. Based on our findings and literature review a risk-stratified approach to diaphragmatic complications is proposed.